The effects of resistance training with or without peanut protein supplementation on skeletal muscle and strength adaptations in older individuals. Issue 1 (14th December 2020) - Lamb, Donald A.; Moore, Johnathon H.; Smith, Morgan A.; Vann, Christopher G.; Osburn, Shelby C.; Ruple, Bradley A.; Fox, Carlton D.; Smith, Kristen S.; Altonji, Olivia M.; Power, Zade M.; Cerovsky, Annsley E.; Ross, C. Owen; et al.
Abstract: Several studies suggest resistance training (RT) while supplementing with various protein supplements can enhance strength and muscle mass in older individuals. However, to date, no study has examined the effects of RT with a peanut protein powder (PP) supplement on these outcomes. Herein, 39 older, untrained individuals ( n  = 17 female, n  = 22 male; age = 58.6 ± 8.0 years; body mass index =28.7 ± 5.8) completed a 6-week ( n  = 22) or 10-week ( n  = 17) RT program, where full-body training was implemented twice weekly (ClinicalTrials.gov trial registration NCT04015479; registered July 11, 2019). Participants in each program were randomly assigned to consume either a PP supplement once per day (75 total g powder providing 30 g protein, > 9.2 g essential amino acids, ~ 315 kcal; n  = 20) or no supplement (CTL; n  = 19). Right leg vastus lateralis (VL) muscle biopsies were obtained prior to and 24 h following the first training bout in all participants to assess the change in myofibrillar protein synthetic rates (MyoPS) as measured via the deuterium-oxide (D2 O) tracer method. Pre- and Post-intervention testing in all participants was conducted using dual energy x-ray absorptiometry (DXA), VL ultrasound imaging, a peripheral quantitative computed tomography (pQCT) scan at the mid-thigh, and right leg isokinetic dynamometer assessments. Integrated MyoPS rates over a 24-h period were not significantly different ( p  < 0.05) between supplement groups following the first training bout. Regarding chronic changes, there were no significant supplement-by-time interactions in DXA-derived fat mass, lean soft tissue mass or percent body fat between supplementation groups. There was, however, a significant increase in VL thickness in PP versus CTL participants when the 6- and 10-week cohorts were pooled (interaction p  = 0.041). There was also a significant increase in knee flexion torque in the 10-week PP group versus the CTL group (interaction p  = 0.032). In conclusion, a higher-protein, defatted peanut powder supplement in combination with RT positively affects select markers of muscle hypertrophy and strength in an untrained, older adult population. Moreover, subanalyses indicated that gender did not play a role in these adaptations.